Pragmatic Analysis of Leech’s Politeness Principles in Encanto Movie - Tri Vika Siahaan; Geby Novelisa Sitompul; Gifa Auzira Alivia; Jesika br Sitio (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
This study explores how politeness works in the animation movie called Encanto in theory of Geoffrey Leech’s Politeness Principle. It focuses on how the six maxims of tact, generosity, approbation, modesty, agreement, and sympathy appear in the characters’ dialogues and how they build the story and their relationships. The data collected from selected lines in the movies and were analyzed using a qualitative descriptive method. The researchers identified the dialogues that presented politeness, classified them based on Leech’s maxims, and analyzed how each maxim functions in the characters’ communications. This helps us know how polite language can reduce tension and guide emotional responses during conversations. It also shows how everyday family talk reflects values like respect, care, and modesty. The findings reveal that all six maxims appear in the film, with approval being the most frequent and sympathy the least. In more emotional scenes, the characters tend to rely on tact and generosity. The approval maxim often helps maintain relationships and encourages warmth between characters. Overall, the study suggests that politeness in Encanto supports family harmony and plays an important role in character development and conflict resolution. It also shows that pragmatic theories can be applied to fictional stories and adds to the growing research on politeness in animated films.